Gestión de riesgos mayores para mejorar la capacidad de respuesta del Centro de Salud N.-3 perteneciente al Distrito Chambo-Riobamba. - Jorge Luis, Amanta Mejicano (2018)
emergency, establishing methods to be followed, if it is raised in the health center N.- 3 Belonging to the Chambo-Riobamba district, mainly protecting the physical integrity of people. For these reasons, the analysis was carried out with the different methods and tools necessary to fulfill the main objective of this research, which is to determine the risks, threats and degree of vulnerability that the facilities have and to carry out the management of major risks; the identification and data collection was made to determine the type of infrastructure and materials stored, and the level of risk that was presented, applying the different methods such as: Method MEIPEE this determined the existing risks in the center of Health N.- 3 Belonging to the district Chambo-Riobamba the same that were: risk before earthquakes and risk to fires with a high qualification. MESERI method has an average risk of 5.49, its interpretation says that it is within the range of 4.1 to 6. Showing an acceptable average risk level. NFPA method lets us know the fuel load of each area. The most vulnerable area is the warehouse and maintenance since it has a high risk. The proposal for an emergency plan for human planning and organization is left for the optimal use of the technical means provided in order to minimize the consequences that could arise from the emergency situation.